Relationship between Professional Ethics and Job Commitment - K Niazazari; T Enayati; R Behnamfar; Z Kahroodi (Iran University of Medical Sciences, 2014)
Abstract   Background & Aim: Professional ethic has a significant effect on individual and group performance and organizational results. The aim of this study was to investigate the relationship between organizational commitment and professional ethics.   Materials & Methods: It was a descriptive-correlational study. The sample consisted of 226 persons including nurses and administrative personnel (ward clerks, medical records employees...) of Imam Reza hospital in Amol city. They were randomly selected according to Krejcie and Morgan table and responded to Ali professional ethic questionnaire and Allen and Myer organizational commitment questionnaire. Data was analyzed by Pearson correlation and simple linear regression analysis tests using SPSS-PC (v. 16).   ‎ Results: The results showed that professional ethic has a positive significant relationship with organizational commitment and it's three dimensions (Affective, Continuance, Normative). Professional ethic also could predict organizational commitment (P<0/001), in such a way that an increase of one grade in professional ethics, will increase 0/284 grade in commitment mean. Conclusion: According to the findings, it is recommended that the managers of care organizations emphasis on general and specific aspects of professional ethic according to different jobs and as a role model act as a pioneer in consideration of ethic in their performance.